FAKTOR FINANSIAL DAN NON FINANSIAL MEMPENGARUHI RENTABILITAS PADA LEMBAGA PERKREDITAN DESA (LPD) DI KABUPATEN JEMBRANA PERIODE TAHUN 2011-2013 - Ni Ketut Narti; I Wayan Sukarta; Luh Made Wijayati; Ni Ketut Lasmini (Forum Manajemen STIMI Handayani Denpasar, 2015)
Lembaga Perkreditan Desa (LPD) is a financial institution owned Pakramanin Bali. Formation of Lembaga Perkreditan Desa (LPD) is the government’s effortsto address the economic disparities in urban areas with rural areas, especially inBali. The success of an LPD can not be separated from the LPD’s ability to obtainprofit. Healthy least LPD can be measured by indicators of rentabilitas. rentabilitasof a company is shown by a comparison between profits with the capital to generateprofits. This study aimed to determine the effect of cash flows, the effectiveness ofdebt management, loan to deposit ratio, the number of customers and the locationof the rentabilitas of the LPD in Jembrana Regency period in 2011-2013 eithersimultaneously or partially. Data analysis techniques used in this research is multiplelinear regression analysis technique analysis results Ŷ =0,026 + 0,001 X + 0,532X2+ 0,672 X3 + 0,005 X4 - 0,083 X. F test analysis results indicate that the variablerate cash flows, the effectiveness of debt management, loan to deposit ratio, thenumber of customers and locations simultaneously influence on rentabilitas in theLPD in Jembrana Regency period 2011-2013. T test showed that the effectiveness ofdebt management (3,207) and loan to deposit ratio (17,101) is significant positiveeffect on rentabilitas while the level of cash turnover(0,792), the number of customers(0,229) and location (-1,669)did not show any significant effect on rentabilitas, buthas a positive direction in accordance with the hypothesized.